ANALISIS BEBAN KERJA MENGGUNAKAN METODE NATIONAL AERONAUTICS AND SPACE ADMINISTRATION TAKS LOAD INDEX DI PT XYZ PURWAKARTA - Aldo Fauzi Dherryawan; Asep Hermawan; Dedy Setyo Oetomo (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
Currently, companies are required to compete in maintaining the existence of customer satisfaction so that the company can survive amidst intense competition. In order to maintain intense competition, productivity in the production line must be increased. The impact of increasing activity on the production line is that the workload on production employees increases, which causes several problems. One of the problems faced by employees is excessive workload due to physical and mental stress. Conditions like this are being experienced by PT XYZ Purwakarta. From this condition, it is necessary to carry out a workload analysis. One of the appropriate workload methods for this analysis is the National Aeronautics and Space Administration Tax Load Index (NASA TLX) workload analysis method. NASA TLX is a workload analysis method used to analyze the mental workload faced by workers with several indicators that are used as assessments such as mental demand (MD), physical demand (PD), temporal demand (TD), performance (P), effort ( EF) and frustrated level (FR) (Hart & Stavelend, 1988).